Short Bones, Renal Stones, and Diagnostic Moans: Hypercalcemia in a Girl Found to Have Coffin-Lowry Syndrome - Christina G. Tise MD, PhD; Dena R. Matalon MD; Melanie A. Manning MD; Heather M. Byers MD; Monica Grover MBBS (SAGE Publishing, 2022)
Pathogenic variants in RPS6KA3 are associated with Coffin-Lowry syndrome (CLS), an X-linked semidominant disorder characterized by intellectual disability, stimulus-induced drop attacks, distinctive facial features, progressive kyphoscoliosis, and digit anomalies in hemizygous males. Heterozygous females may also have features of CLS; however, there can be considerable phenotypic variation, often attributed to ratios of X-inactivation in various tissue types. Although skeletal anomalies and short stature are hallmarks of CLS, hypercalcemia has not been reported. Here we describe a 30-month-old girl with gross motor delays, short stature, dysmorphic features, bilateral duplicated renal collecting systems, and no family history of hypercalcemia who required multiple admissions for idiopathic hypercalcemia necessitating bisphosphonate infusions at 12.5 and 15 months of age. A maternally inherited likely-pathogenic variant in RPS6KA3 was identified by trio exome sequencing, consistent with the diagnosis of CLS in the proband and her mother. Maternal history was notable only for decreased height compared to first-degree relatives, bilateral genu valgum, and a bicornuate uterus; she was later found to also have a partially duplicated left renal collecting system. Subsequent X-inactivation studies in blood aligned with the phenotypic variation between mother and daughter. Although hypercalcemia is not a reported feature in CLS, there is evidence of interrupted osteoblast differentiation, providing a potential mechanism for hypercalcemia in this genetic condition. The hypercalcemia in this case may represent a severe presentation of an unrecognized clinical feature in CLS that resolves with age. This case further highlights the intrafamilial phenotypic variation of CLS among females, suggesting X-inactivation as the underlying mechanism, and demonstrates the value of exome sequencing in patients for whom a genetic disorder is highly suspected but not identified despite thorough evaluation.